Manipulating Polymer Backbone Configuration via Halogenated Asymmetric End-Groups Enables Over 18% Efficiency All-Polymer Solar Cells - Guo, Jing (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 Wiley-VCH GmbH.